Carbon-coated efficient and stable platinum-based alloy nano-catalyst as well as preparation method and application thereof

By using the use of carbon coating type high -efficiency stable and stable platinum -based alloy nano -catalysts in the fuel cell catalyst, the oxidation and dissolution of catalysts in high voltage and strong acidic conditions are solved, and the improvement of catalytic activity and cycle stability have been achieved. Suitable for the application of fuel cells.

CN119361732APending Publication Date: 2025-01-24QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411452513.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing fuel cell catalysts are prone to oxidation, dissolving and loss under high voltage and strong acid conditions, resulting in a decrease in catalytic activity and a shortened membrane electrode life.

Method used

The preparation method of carbon coverage high -efficiency and stable platinum base alloy nano -catalysts can be used to add transition metal and rare earth metal salts to the front drive of the organic polymer, and use the chelating effect of organic weak acid root to achieve the uniform planting of metal elements Entry and in -situ alloy, eventually obtained a composite catalyst catalyst with a platinum -based alloy nanoparticles with a carbon coated layer.

Benefits of technology

The electrocatalytic activity and cycle stability of the catalyst are improved, the catalytic performance of the cathode redox reaction of the fuel cell is enhanced, and the life of the membrane electrode is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361732A_ABST
    Figure CN119361732A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemistry, and particularly relates to a carbon-coated efficient and stable platinum-based alloy nano-catalyst as well as a preparation method and application thereof. The preparation method of the catalyst comprises the following steps: in the process of preparing an organic polymer precursor, adding transition metal and rare earth metal salts, and uniformly implanting the added metal elements into the organic polymer precursor through the ligand chelation of organic weak acid radicals; then performing high-temperature pyrolysis and carbonization to obtain a porous carbon carrier with carbon layer coated transition metal particles and rare earth element oxide distribution; and taking the porous carbon as a carrier, dipping in a platinum salt solution, and carrying out reducing atmosphere heat treatment to realize migration of reduced platinum and rare earth elements to the surfaces of carbon-coated transition metal particles and realize in-situ alloying, thereby finally obtaining the platinum-based alloy nanoparticle composite catalyst with the carbon coating layer. The preparation method is simple and effective, and has a wide application prospect in the field of new energy such as hydrogen energy based on the unique structural characteristics of the obtained catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemistry, and in particular relates to a carbon-coated, efficient and stable platinum-based alloy nanocatalyst, a preparation method and an application thereof. Background Art

[0002] Hydrogen energy technology is one of the key technologies for carbon reduction, and it is also the key to the competition in the new round of scientific and technological revolution and industrial transformation. Fuel cell technology, as the core technology of the hydrogen energy industry, especially proton exchange membrane fuel cells, is widely used in the fields of transportation, power supply and portable power supply, and is generally considered to be one of the key technologies to solve the future energy crisis of mankind. However, its catalyst is still mainly platinum. In order to further reduce costs and reduce the amount of platinum catalyst, Pt is usually alloyed with other transition metals, such as Fe, Co, Ni and other transition metal elements, and the ligand effect and stress effect are used to improve the catalyst performance and reduce the amount of Pt used. Both effects can move the d-band center of gravity of Pt atoms downward, weaken the binding energy of Pt with oxygen-containing intermediates, and improve catalytic activity.

[0003] Currently, the most common high-activity catalysts are Pt-based alloy catalysts. However, under the harsh working conditions of fuel cells, under high voltage and strong acid working conditions, the transition metals in the catalyst are very easy to oxidize and dissolve, resulting in the disappearance of the ligand effect and stress effect brought by alloying, and the catalytic activity decreases. The dissolved ions may attack the proton membrane, resulting in a reduction in the life of the membrane electrode in later applications. Therefore, it is very important to develop new preparation strategies to achieve controllable preparation of efficient, stable, and functional doped alloy catalysts for the development of fuel cell technology. Summary of the invention

[0004] To achieve the above-mentioned purpose, the present invention provides a carbon-coated, efficient and stable platinum-based alloy nanocatalyst and its preparation method and application

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a carbon-coated, efficient and stable platinum-based alloy composite nanocatalyst comprises the following steps: in the process of preparing an organic polymer precursor, adding transition metal and rare earth metal salts, and uniformly implanting the added metal elements into the organic polymer precursor through the ligand chelation of organic weak acid radicals, followed by high-temperature pyrolysis and carbonization to obtain a porous carbon carrier having transition metal particles coated with a carbon layer and rare earth element oxide distribution; using the porous carbon as a carrier, impregnating a platinum salt solution and subjecting the porous carbon to heat treatment in a reducing atmosphere, achieving the migration of reduced platinum and rare earth elements to the surface of the carbon-coated transition metal particles and achieving in-situ alloying, and finally obtaining a platinum-based alloy nanoparticle composite catalyst having a carbon coating layer.

[0007] The porous carbon carrier is prepared by adding transition metals, rare earth metal salts and organic weak acids as chelating agents during the preparation of organic polymer precursors. During the self-assembly polymerization of organic molecules in the system, transition metal salts and rare earth elements are confined and complexed with organic weak acid radicals to form a precursor, which is then calcined and pyrolyzed at high temperature to obtain a porous carbon substrate with transition metal particles protected by a carbon layer and uniformly distributed rare earth oxides.

[0008] Furthermore, the chelating agent, transition metal and rare earth metal salt are dissolved in a solvent respectively, and then mixed with the raw materials for preparing the precursor and stirred for 1 to 24 hours respectively. During the self-assembly polymerization of organic molecules in the mixed system, the chelating agent produces coordination complexation with the transition metal salt and the rare earth element and is uniformly embedded in the organic polymer in situ. Subsequently, the obtained precursor is calcined in an inert atmosphere to obtain a porous carbon carrier with a carbon layer coating transition metal particles and rare earth element oxide distribution; wherein the calcination temperature is 700 to 1000°C and the calcination time is 2 to 6 hours.

[0009] The organic polymer precursor is one or more of a monomer polymer, a polymer or a metal organic framework polymer; wherein the monomer polymer is one or more of small molecule indene, dopamine, aniline, pyrrole, thiophene, pyridine; the polymer is a polymer formed by polycondensation between any two or more resin molecules; for example, phenolic resin, urea-formaldehyde resin, polyamide resin, etc. The metal organic framework polymer is one or more of ZIF-8, ZIF-67, COFs.

[0010] The chelating agent is one or more of the organic acids ethylenediaminetetraacetic acid, diacetic acid triaminepentaacetic acid, benzoic acid, citric acid, 1,2-cyclohexanediaminetetraacetic acid, o-hydroxyphenylacetic acid, hydroxyethylethylenediaminetriacetic acid, and the metal salts corresponding to the above substances; the solvent is water, alkane, ketone or organic alcohol, wherein the alkane is n-hexane, cyclohexane, hexane, etc., the ketone is acetone, etc., and the organic alcohol is ethanol, isopropanol, n-butanol, etc.

[0011] The molar ratio of the added chelating agent to the metal salt is 1:10 to 10:1; the added chelating agent accounts for 1.0 wt.% to 50 wt.% of the total mass of the precursor.

[0012] Furthermore, a platinum salt solution is added to a porous carbon carrier having a carbon layer coated with transition metal particles and a distribution of rare earth element oxides, so that equal volumes are impregnated to form a slurry, which is then placed in a freeze dryer for drying after ultrasonic treatment, and the dried product is then placed in a tubular furnace for pyrolysis and carbonization treatment, and after cooling to room temperature, a rare earth-doped platinum-based alloy nanoparticle composite catalyst with a carbon coating layer is obtained; wherein the molar ratio of platinum to transition metal elements is 4:1 to 0.5:1, and the types of transition metal elements are Fe, Co, Ni, Cu, Zn, Y, Nb, Ru, and Pd; the molar ratio of platinum to rare earth elements is 10:1 to 1:1, and the rare earth elements are mainly Gd, Tb, Sm, Nd, Pm, Ce, and La.

[0013] The calcination atmosphere is an inert atmosphere or a reducing atmosphere, wherein the inert atmosphere is a mixture of one or more of nitrogen, argon, and helium, and the reducing atmosphere is a mixture of an inert atmosphere and a reducing gas; the calcination temperature is 700-1000° C., and the calcination time is 2-6 hours; the theoretical content of platinum accounts for 5-60wt.% of the final catalyst mass.

[0014] The solvent used in the platinum salt solution is one or more of distilled water, methanol, ethanol, propanol and isopropanol.

[0015] The reducing atmosphere is a H2 / Ar mixed gas with a hydrogen ratio of 1.0 at.% to 50 at.%; the temperature of the reducing heat treatment is 300 to 1000°C; and the time of the reducing heat treatment is 1 to 10 hours.

[0016] A carbon-coated, efficient and stable platinum-based alloy nanocatalyst prepared by the method can prepare a carbon-coated, efficient and stable platinum-based alloy nanocatalyst with uniform particle distribution and fine particle size.

[0017] An application of the carbon-coated high-efficiency and stable platinum-based alloy nanocatalyst, and application of the catalyst in a fuel cell.

[0018] Compared with the prior art, the creativity of the present invention is specifically embodied in the following aspects:

[0019] The preparation method adopted by the present invention is simple and effective. Based on the unique structural characteristics of the obtained catalyst, including smaller catalyst particle size and uniform diameter distribution, trace stabilized rare earth element doping and ordered platinum alloy structure, it has excellent catalytic activity and cycle stability for the cathode redox reaction of fuel cells and has potential application prospects in fuel cells. Specifically:

[0020] (1) The present invention prepares a carbon-supported platinum-based alloy composite catalyst through an in-situ alloying strategy, introduces transition metal and rare earth metal elements by utilizing the ligand chelation effect of organic acid radicals, and then performs pyrolysis and carbonization to obtain transition metal particles / rare earth metal oxide-mesoporous carbon, wherein the transition metal particles are present in a carbon substrate in a carbon-coated form.

[0021] (2) The method of the present invention can regulate the surface charge and electronic structure of platinum by doping platinum alloy nanoparticles with rare earth metal elements, thereby enhancing the electrocatalytic activity and stability of the catalyst;

[0022] (3) The porous carbon substrate prepared by the method of the present invention can disperse Pt to the maximum extent during the impregnation of Pt salt, so that the reduced Pt-based alloy particles are small and no agglomeration occurs;

[0023] (4) The catalyst prepared by the method of the present invention has a catalytic activity superior to that of commercial platinum carbon and has good application prospects in the fields of fuel cells and industrial catalysis.

[0024] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : is a SEM image of transition metal and rare earth oxide doped mesoporous carbon prepared in Example 1 of the present invention.

[0026] Figure 2 This is a TEM image of the mesoporous carbon-supported Gd-doped PtFe alloy catalyst prepared in Example 1 of the present invention.

[0027] Figure 3 This is the XRD pattern of the mesoporous carbon and Gd-doped PtFe alloy catalyst prepared in Example 1 of the present invention.

[0028] Figure 4 This is the oxygen reduction curve diagram after preparation in Example 1 of the present invention.

[0029] Figure 5 This is a mass activity comparison chart of the Gd-doped PtFe alloy catalyst prepared in Example 1 of the present invention after stability testing.

[0030] Figure 6 TEM image of the La and Co doped mesoporous carbon support prepared in Example 2 of the present invention and the XRD pattern of the formed carbon-supported platinum-based alloy catalyst. DETAILED DESCRIPTION

[0031] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0032] The present invention is based on the coordination characteristics of organic acid radicals with polymer precursors and metal salts, and combines in-situ alloying strategies to prepare carbon-supported rare earth-doped platinum-based alloy composite catalysts, specifically:

[0033] Organic acid radicals are used as ligand chelating agents to introduce transition metals and rare earth metal elements, and an organic polymer precursor doped with transition metals and rare earth metal elements is prepared. A solution containing organic acid radicals and metal salts is added to the corresponding polymer solution system. The obtained precursor containing the metal salt organic acid radical complex is then pyrolyzed and carbonized under an inert atmosphere to obtain mesoporous carbon loaded with rare earth metal oxides. Platinum salts are introduced by impregnation using the mesoporous carbon as a carrier, and further reduction heat treatment is performed in a H2 / Ar mixed gas to obtain platinum alloy nanoparticles doped with rare earth elements.

[0034] The preparation method adopted by the present invention is simple and effective. Based on the unique structural characteristics of the obtained catalyst, including smaller catalyst particle size and uniform diameter distribution, trace stabilized rare earth element doping and ordered platinum alloy structure, it has excellent catalytic activity and cycle stability for the cathode redox reaction of fuel cells and has potential application prospects in fuel cells.

[0035] Example 1

[0036] 10 mmol zinc nitrate and 1 mmol gadolinium nitrate were weighed and dissolved in 70 mL methanol, and ultrasonic dispersion was performed to form solution A; 40 mmol 2-methylimidazole and 4 mmol sodium ferric ethylenediaminetetraacetate were weighed and dissolved in 50 mL methanol, and then the two solutions were mixed and stirred for 18 h, and the Gd / Fe / ZIF-8 sample was obtained by centrifugation. After freeze-drying, it was calcined in nitrogen at 900 ° C for 4 h to obtain a mesoporous carbon substrate with iron nanoparticles protected by a carbon layer and distributed with Gd2O3 nanoparticles (see Figure 1 Medium and low magnification scanning images (a) and transmission electron microscopy images (b).

[0037] A certain amount of chloroplatinic acid aqueous solution was ultrasonically impregnated into the pores of the prepared mesoporous carbon substrate to form an equal volume impregnation slurry, which was then placed in a freeze dryer for freeze drying. The dried product was then placed in a tube furnace and calcined at 700°C for 4h in a H2 / Ar mixed gas atmosphere with a hydrogen volume content of 5at.%, and then cooled to room temperature to obtain the final catalyst (see Figure 2 The morphology of the prepared mesoporous carbon-supported Gd-doped platinum-iron alloy catalyst was observed by transmission electron microscopy (TEM). Figure 2 As shown in (a), the average particle size of the platinum iron prepared in this embodiment is 2.5 nm, and the particle size distribution is relatively uniform. Figure 2 (b) The high-resolution transmission electron microscopy image clearly shows that the platinum alloy particles are evenly distributed on the carbon substrate, and there is a very thin carbon protective layer around the particles. Figure 3 XRD can be observed in the carbon matrix of Gd2O3 and Fe, the synthesized PtFe-based alloy particles have good crystallinity, broad diffraction peaks and complete crystal plane index.

[0038] The catalyst prepared above was subjected to linear voltammetric scanning in 0.1M HClO4 saturated with oxygen and nitrogen respectively using an electrochemical three-electrode system at a scan rate of 10 mV / s and an electrode rotation speed of 1600 rpm. The voltammetric curve in 0.1M HClO4 saturated with oxygen was then subtracted from the voltammetric curve in 0.1M HClO4 saturated with nitrogen (see Figure 4 ). The test methods for the ORR performance of the catalysts involved in the present invention in acidic media are the same as the above test methods. The catalyst prepared in this example shows excellent ORR performance in acidic media, with an ORR starting potential of 1.0V vs.RHE and an ORR half-wave potential of 0.92Vvs.RHE. The ORR stability is better than that of the commercial Pt / C catalyst (JM, 20wt%) (see Figure 4 ).

[0039] The catalyst prepared above was subjected to a three-electrode system in an oxygen-saturated 0.1M HClO4 solution, in the voltage range of 0.6-0.95V, at a scan rate of 100mV / s for 100,000 cycles of cycling stability testing. The test results are as follows: Figure 5 As shown, after 100,000 cycles of long-term stability testing, the catalyst stability did not show obvious attenuation, and the stability and activity were significantly improved compared with commercial Pt / C catalysts.

[0040] Example 2

[0041] First, in a dry 250mL beaker, 8.6mL of concentrated hydrochloric acid was slowly added to 90mL of deionized water and stirred thoroughly to ensure that the hydrochloric acid was completely dissolved to form a 1mL / L colorless and transparent hydrochloric acid solution. Next, the solution was transferred to a 100mL volumetric flask for constant volume for subsequent use. Subsequently, 50mL was taken from the hydrochloric acid solution and placed in another beaker, 84mg (0.1mmol) of disodium ethylenediaminetetraacetate and 4.7mL (0.05mmol) of aniline were added, and stirred at room temperature for 10 minutes to ensure that the aniline was evenly dispersed to form solution A.

[0042] At the same time, in another beaker, 4.5 mg (0.0125 mmol) of lanthanum nitrate and 30 mg of cobalt nitrate were added to another 50 mL of 1 mL / L hydrochloric acid solution, and stirred for 10 minutes until lanthanum nitrate and cobalt nitrate were completely dissolved to form solution B. Subsequently, solution A was mixed with solution B and stirred continuously, and 1 mL of 30% hydrogen peroxide solution was added at one time using a pipette to promote the oxidative polymerization reaction of aniline to generate a cobalt lanthanum-doped polyaniline precursor, and the obtained cobalt lanthanum-doped polyaniline precursor was left open at room temperature (25 ° C) for 24 hours to precipitate the precursor. After precipitation, the pH value of the solution was adjusted to 7.0 using 1 mL / L sodium hydroxide solution to neutralize the unreacted acidic substances. Then, the precipitate was separated by low-temperature centrifugation, the supernatant was removed, and the precipitate was washed three times with deionized water to remove impurities.

[0043] Finally, the cleaned cobalt-lanthanum-doped polyaniline precursor was placed in a vacuum drying oven and dried at 65°C for 2 hours, then calcined at 900°C for 4 hours in a H2 / Ar mixed gas atmosphere with a hydrogen volume content of 5 at.%, and finally cooled to room temperature to obtain a porous carbon support with cobalt nanoparticles and lanthanum oxide distribution. The TEM images of the La- and Co-doped mesoporous carbon support are shown in FIG. Figure 6 (a) shown.

[0044] A certain amount of aqueous solution of chloroplatinic acid is ultrasonically impregnated into the pores of the porous carbon carrier distributed with cobalt nanoparticles and lanthanum oxide prepared above to form an equal volume impregnation slurry, which is then placed in a freeze dryer for freeze drying. The dried product is then placed in a tube furnace and calcined at 750°C for 3h in an atmosphere of H2 / Ar mixed gas with a hydrogen volume content of 10at.%, and then cooled to room temperature to obtain the final catalyst. The X-ray derivative spectrum of the catalyst is as follows: Figure 6 As shown in (b), it can be seen that the final catalyst is pure in phase, with fine particles and good repeatability.

[0045] Example 3

[0046] Weigh 30 mg of anhydrous ferric chloride and 10 mg of neodymium chloride and dissolve them in 100 mL of chloroform. After ultrasonic dispersion for 30 minutes, place the reaction bottle in a zero degree Celsius constant temperature reaction bath and stir continuously to form solution A. Disperse 500 mg of thiophene and 50 mg of sodium citrate in 500 mL of chloroform under a nitrogen atmosphere and stir ultrasonically to form solution B. Pour solution B into solution A for polymerization for 12 hours at a stirring rate of 100 rpm. After the polymerization reaction is completed, acetone is added to terminate the reaction, and the polymer is collected by centrifugation after standing for 2 hours. The obtained solid polymer material is washed with dilute hydrochloric acid (0.10 mol / L), acetone, anhydrous ethanol and deionized water in turn to remove impurities in the sample. Finally, the obtained sample is placed in a vacuum oven and dried at 50 ° C for 24 hours to obtain a polythiophene sample co-doped with Nd and Fe. The dried polythiophene sample is pyrolyzed and carbonized at 1000 ° C for 3 hours in an Ar gas atmosphere, and finally cooled to room temperature to obtain a porous carbon carrier distributed with iron nanoparticles and neodymium oxide.

[0047] The above-mentioned porous carbon carrier is used as the carbon substrate, and a certain amount of aqueous solution of chloroplatinic acid is ultrasonically impregnated into the pores of the prepared mesoporous carbon substrate to form an equal volume impregnation slurry, which is then placed in a freeze dryer for freeze drying. The dried product is then placed in a tubular furnace and calcined at 800°C for 3h in an atmosphere of H2 / Ar mixed gas with a hydrogen volume content of 15at.%, and then cooled to room temperature to obtain the final catalyst.

[0048] In summary, in the process of preparing the precursor, the catalyst of the present invention introduces the transition metal elements and a small amount of doped rare earth elements that can be alloyed with platinum into the precursor through the coordination and chelation of organic weak acid radicals of different molecular weights and realizes their high dispersion, and then performs high-temperature pyrolysis to obtain transition metal particles with a carbon layer coating structure and a carbon carrier distributed with rare earth metal oxides. Finally, the platinum ions and rare earth elements are migrated to the surface of the transition metal particles to form alloys through the impregnation in-situ alloying strategy to obtain a carbon-coated platinum-based alloy composite catalyst. The unique structural features of the obtained catalyst include smaller catalyst particle size and uniform diameter distribution, trace stabilized rare earth element doping and platinum-based alloy ordered structure, which has excellent catalytic activity and cycle stability for redox reaction and hydrogen evolution reaction in different pH solutions, and has broad application prospects in new energy fields such as hydrogen energy.

Claims

1. A method for preparing a carbon-coated, efficient and stable platinum-based alloy composite nanocatalyst, characterized in that: In the process of preparing an organic polymer precursor, transition metal and rare earth metal salts are added and the added metal elements are uniformly implanted into the organic polymer precursor through the ligand chelation of organic weak acid radicals, followed by high-temperature pyrolysis and carbonization to obtain a porous carbon carrier having a carbon layer-coated transition metal particles and a distribution of rare earth element oxides; the porous carbon is used as a carrier, impregnated with a platinum salt solution and subjected to a reducing atmosphere heat treatment to achieve the migration of reduced platinum and rare earth elements to the surface of the carbon-coated transition metal particles and to achieve in-situ alloying, and finally to obtain a platinum-based alloy nanoparticle composite catalyst with a carbon coating layer.

2. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 1, characterized in that: The porous carbon carrier is prepared by adding transition metals, rare earth metal salts and organic weak acids as chelating agents during the preparation of organic polymer precursors. During the self-assembly polymerization of organic molecules in the system, transition metal salts and rare earth elements are confined and complexed with organic weak acid radicals to form a precursor, which is then calcined and pyrolyzed at high temperature to obtain a porous carbon substrate with transition metal particles protected by a carbon layer and uniformly distributed rare earth oxides.

3. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 2, characterized in that: The chelating agent, transition metal and rare earth metal salt are dissolved in a solvent respectively, and then mixed with the raw materials for preparing the precursor for stirring for 1 to 24 hours respectively. During the self-assembly polymerization of organic molecules in the mixed system, the chelating agent produces coordination complexation with the transition metal salt and the rare earth element and is uniformly embedded in the organic polymer in situ. Subsequently, the obtained precursor is calcined in an inert atmosphere to obtain a porous carbon carrier with transition metal particles coated with a carbon layer and rare earth element oxide distribution; wherein the calcination temperature is 700 to 1000°C and the calcination time is 2 to 6 hours.

4. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 3, characterized in that: The organic polymer precursor is one or more of a monomer polymer, a polymer or a metal organic framework polymer; wherein the monomer polymer is one or more of small molecule indene, dopamine, aniline, pyrrole, thiophene, and pyridine; the polymer is a polymer formed by condensation polymerization between any two or more resin molecules; the metal organic framework polymer is one or more of ZIF-8, ZIF-67, and COFs.

5. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 3, characterized in that: The chelating agent is one or more of organic acids such as ethylenediaminetetraacetic acid, diacetic acid, triaminepentaacetic acid, benzoic acid, citric acid, 1,2-cyclohexanediaminetetraacetic acid, o-hydroxyphenylacetic acid, hydroxyethylethylenediaminetriacetic acid, and metal salts corresponding to the above substances; the solvent is water, alkane, ketone or organic alcohol.

6. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 3, characterized in that: The molar ratio of the added chelating agent to the metal salt is 1:10 to 10:1; the added chelating agent accounts for 1.0 wt.% to 50 wt.% of the total mass of the precursor.

7. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 1, characterized in that: A platinum salt solution is added to a porous carbon carrier having a carbon layer coated with transition metal particles and a distribution of rare earth element oxides, so that equal volumes are impregnated to form a slurry, and then the slurry is placed in a freeze dryer for drying after ultrasonic treatment. The dried product is then placed in a tubular furnace for pyrolysis and carbonization treatment, and after cooling to room temperature, a rare earth-doped platinum-based alloy nanoparticle composite catalyst with a carbon coating layer can be obtained; wherein the molar ratio of platinum to transition metal elements is 4:1-0.5:1, and the types of transition metal elements are Fe, Co, Ni, Cu, Zn, Y, Nb, Ru, and Pd; the molar ratio of platinum to rare earth elements is 10:1-1:1, and the rare earth elements are mainly Gd, Tb, Sm, Nd, Pm, Ce, and La.

8. The method for preparing the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 7, characterized in that: The calcination atmosphere is an inert atmosphere or a reducing atmosphere, wherein the inert atmosphere is a mixture of one or more of nitrogen, argon, and helium, and the reducing atmosphere is a mixture of an inert atmosphere and a reducing gas; the calcination temperature is 700-1000° C., and the calcination time is 2-6 hours; the theoretical content of platinum accounts for 5-60wt.% of the final catalyst mass.

9. A carbon-coated, efficient and stable platinum-based alloy nanocatalyst prepared by the method of claim 1, characterized in that: The method of claim 1 is used to prepare a carbon-coated, highly efficient and stable platinum-based alloy nanocatalyst with uniform particle distribution and fine particle size.

10. An application of the carbon-coated, efficient and stable platinum-based alloy nanocatalyst according to claim 9, characterized in that: Application of the catalyst in a fuel cell.

Citation Information

Cited By

  • Preparation method for precisely constructing transition-rare earth bimetallic monatomic material based on confinement strategy of soft-hard acid-base theory and application of transition-rare earth bimetallic monatomic material in lithium-oxygen battery

    CN121583931A